Organizational climate and work performance of the health personnel at the Daniel Alcides Carrión Hospital, Pasco - Rojas Livia, Sely (2019)
Objectives. To determine the relationship between organizational climate and work performance. Methods. Correlational, cross-sectional study, with a quantitative approach, made up of 234 health workers from the daniel alcides carrión hospital, in the department of pasco, during the 2018 period. an organizational climate scale and a performance evaluation sheet were used. pearson’s correlation coefficient r was used in the inferential analysis. Results. 83.3% (195 workers) showed organizational climate to be improved and 49.1% (115 workers) showed average work performance, on the other hand, the organizational climate is significantly related to the work performance of the health personnel under study, with p<= 0.000. and the work performance is significantly related to the organizational climate in the human potential dimension (p<= 0.000), organizational design (p<= 0.002) and organizational culture (p<= 0.004). Conclusions. The organizational climate is related to the work performance of health personnel at the daniel alcides carrión hospital, pasco.